Novel pathogenic ATM mutation with ataxia-telangiectasia in a Chinese family - Zhou, Qiaomin; Chen, Minling; Tao, Enfu (Frontiers in Genetics, 2024)
Ataxia-Telangiectasia (A-T) is a rare, autosomal recessive disorder characterized by progressive cerebellar ataxia, oculocutaneous telangiectasia, immunodeficiency, and increased cancer risk. Mutations in the ATM gene, which is essential for DNA damage repair, underlie this condition. This study reports a novel homozygous frameshift mutation (ATM_ex20 c.3062delT, p. Val1021fs) in a Chinese family with two affected siblings. The mutation, located in exon 20, has not been previously documented, expanding the spectrum of ATM mutations. The proband and her older sister presented with classic A-T symptoms, including gait instability and conjunctival telangiectasia. Both siblings presented with immunodeficiency, characterized by low immunoglobulin A (IgA) levels, slightly elevated IgM levels, and elevated alpha-fetoprotein (AFP). Cranial magnetic resonance imaging (MRI) findings revealed cerebellar atrophy and cerebral white matter lesions in both sisters. Interestingly, while both sisters shared the same mutation, their clinical severity differed, highlighting the complexity of genotype-phenotype correlations in A-T. The parents and an unaffected sister were heterozygous carriers, consistent with autosomal recessive inheritance. This study underscores the importance of genetic testing in A-T diagnosis and provides new insights into the genetic diversity of ATM-related diseases. Further research is needed to understand the broader implications of this mutation.